Differences in the delivery of the corner in a baby who was bathed in warm water with a baby whipped in a wet tool at batara siang hospital of Pangkep District - Herman, H (International Journal for Educational and Vocational Studies, 2021)
WHO (2000), recommends umbilical cord care based on aseptic and dry principles and no longer recommended to use alcohol but with open care. The umbilical cord should also not be tightly closed with anything, because it will make it moist. In addition to slowing the release of the umbilical cord, it also poses a risk of infection. Even if you have to close. according to Taylor (2003, dalam Nopriyarti, 2013) cover or tie loosely at the top of the umbilical cord with sterile gauze. The research used quasi-experimental research. The design of this study used the Experimental Design- Equivalent Time Sample method, which is a quasi-experimental design by treating the experimental group (X1), namely taking a warm bath and the control group (X0), which was wiped with a wet towel, alternately with random determination (Suharsaputra, 2012). The mandatory output in this research is publishing international journals, while the additional output is publishing national journals it can be seen that the average length of umbilical cord detachment of infants who were bathed in warm water (experimental group) was 110.8 hours, while the average length of time to release the umbilical cord of infants who were wiped with a wet towel (control group) was 76.9 hours or 6.6 days. The average difference between the two groups is 24,72 hours. The results of the statistical test obtained a P-value (<0.001), meaning that at alpha 5% there was a significant difference in the average length of umbilical cord detachment between babies who were wiped with a wet towel, which was 2.01 days and babies who were bathed in warm water, which was 4,01 day. So that the treatment of babies who are wiped with a wet towel is more effective and the umbilical cord is removed faster than the care of babies who are bathed in warm water. There was a significant difference between the In umbilical cord care, there was a significant difference in the average length of umbilical cord detachment between babies who were wiped with a wet towel and babies who were bathed in warm water.